Physiological and pathological left ventricular hypertrophy of comparable degree is associated with characteristic differences of in vivo hemodynamics - Olah, Attila Josef; Németh, Balázs Tamás; Mátyás, Csaba; Hidi, László; Lux, Árpád; Ruppert, Mihály; Kellermayer, Dalma; Sayour, Alex Ali; Szabó, Lilla; Török, Marianna; Meltzer, Anna; Gellér, László; et al. (American journal of physiology. Heart and circulatory physiology, 2016)
Left ventricular (LV) hypertrophy is a physiological or pathological response of LV myocardium to increased cardiac load. We aimed at investigating and comparing hemodynamic alterations in well-established rat models of physiological hypertrophy (PhyH) and pathological hypertrophy (PaH) by using LV pressure-volume (P-V) analysis. PhyH and PaH were induced in rats by swim training and by abdominal aortic banding, respectively. Morphology of the heart was investigated by echocardiography. Characterization of cardiac function was completed by LV P-V analysis. In addition, histological and molecular biological measurements were performed. Echocardiography revealed myocardial hypertrophy of similar degree in both models, which was confirmed by post-mortem heart weight data. In aortic-banded rats we detected subendocardial fibrosis. Reactivation of fetal gene program could be observed only in the PaH model. PhyH was associated with increased stroke volume, whereas unaltered stroke volume was detected in PaH along with markedly elevated end-systolic pressure values. Sensitive indexes of LV contractility were increased in both models, in parallel with the degree of hypertrophy. Active relaxation was ameliorated in athlete's heart, whereas it showed marked impairment in PaH. Mechanical efficiency and ventriculo-arterial coupling were improved in PhyH, whereas they remained unchanged in PaH. Myocardial gene expression of mitochondrial regulators showed marked differences between PaH and PhyH. We provided the first comparative hemodynamic characterization of PhyH and PaH in relevant rodent models. Increased LV contractility could be observed in both types of LV hypertrophy; characteristic distinction was detected in diastolic function (active relaxation) and mechanoenergetics (mechanical efficiency), which might be explained by mitochondrial differences.
First published December 28, 2015
Gesehen am 24.06.2020